Identification of Faba bean genetic loci associated with quantitative resistance to the fungus Botrytis fabae, causal agent of chocolate spot - Webb, Anne; Reynolds, Tom R.; Wright, Tally I. C.; Caiazzo, Rosa; Lloyd, David C.; Thomas, Jane E.; Wood, Thomas A. (Frontiers in Plant Science, 2024)
Introduction Chocolate spot, caused by the ascomycete fungus Botrytis fabae, is a devastating foliar disease and a major constraint on the quality and yield of faba beans (Vicia faba). The use of fungicides is the primary strategy for controlling the disease. However, high levels of partial genetic resistance have been identified and can be exploited to mitigate the disease. Methods The partially resistant V. faba cultivar Maris Bead and susceptible Egyptian accession ig70726 were crossed, and a genetic mapping population of 184 individuals was genotyped in the F2 generation and screened for resistance to B. fabae infection in the F3, F5, and F6 generations in a series of field experiments. A high-density linkage map of V. faba containing 3897 DArT markers spanning 1713.7 cM was constructed. Results Multiple candidate quantitative trait loci (QTLs) in 11 separate regions of the V. faba genome were identified; some on chromosomes 2, 3, and 6 overlapped with loci previously linked to resistance to Ascochyta leaf and pod blight caused by the necrotrophic fungus Ascochyta fabae. A transcriptomics experiment was conducted at 18 h post-inoculation in seedlings of both parents of the mapping population, identifying several differentially expressed transcripts potentially involved in early stage defence against B. fabae, including cell-wall associated protein kinases, NLR genes, and genes involved in metabolism and response to reactive oxygen species. Discussion This study identified several novel candidate QTLs in the V. faba genome that contribute to partial resistance to chocolate spot, but differences between growing seasons highlighted the importance of multi-year phenotyping experiments when searching for candidate QTLs for partial resistance.